Re‐evaluating the evidence for late‐surviving megafauna at Nombe rockshelter in the New Guinea highlands. Issue 3 (16th September 2022) - Prideaux, Gavin J.; Kerr, Isaac A. R.; van Zoelen, Jacob D.; Grün, Rainer; van der Kaars, Sander; Oertle, Annette; Douka, Katerina; Grono, Elle; Barron, Aleese; Mountain, Mary‐Jane; Westaway, Michael C.; Denham, Tim
Abstract: The causes of the Late Pleistocene extinction of most larger‐bodied animals on the Australian continent have long been controversial. This is due, in no small part, to inadequate knowledge of exactly when these species were lost from different ecosystems. The Nombe rockshelter in the highlands of Papua New Guinea is one of very few sites on Sahul with as‐yet‐unrefuted evidence for the survival of megafaunal species until more recently than 40 thousand years (ka) ago. However, our understanding of the age of this site has been based on radiocarbon dating. Here we present new U–Th ages on large marsupial specimens from the deposit and identify a range of postcranial elements to species that include the diprotodontid Hulitherium tomasettii, kangaroo Protemnodon tumbuna and thylacine Thylacinus cynocephalus . Direct U–Th ages of 27–22 ka ago on faunal remains of Protemnodon tumbuna and another large unidentified macropodid are consistent with the existing radiocarbon chronology, yet are minimum ages due to the potential for post‐depositional uptake of 238 U and stratigraphic reworking. Pollen analyses indicate perhumid, montane forests dominated by Nothofagus persisted, with minimal human disturbance from at least c.26–20 ka ago up to the terminal Pleistocene. Collagen fingerprinting (ZooMS) demonstrates the potential of protein‐based identification of megafaunal remains at Nombe in the future. This study leaves open the possibility of extended coexistence between some megafaunal species in the montane rainforests of New Guinea and intermittently visiting groups of people, and underscores the need for further investigation of the Nombe deposit. Although preliminary, these findings reinforce the view that debates regarding megafaunal extinctions on Sahul require a greater appreciation of species‐specific temporalities and the degrees of human impact on diverse habitats across the continent. Résumé: Les raisons de l'extinction, à la fin du Pléistocène, de plusieurs grands animaux sur le continent australien, restent sujettes à controverse. Le manque d'information quant au moment exact de la disparition de ces espèces des écosystèmes est un problème inhérent à ce débat. L'abri‐sous‐roche de Nombe, dans les Hautes Terres de Papouasie Nouvelle‐Guinée, est l'un des rares sites de Sahul attestant clairement de la survie d'une mégafaune jusqu'à une période plus récente que 40 000 ans. Néanmoins, l'âge du site restait jusqu'à présent basé sur des datations radiocarbone. Nous présentons ici de nouvelles datations U/Th obtenues sur des spécimens de marsupiaux provenant de ce dépôt, et identifions plusieurs éléments postcrâniens au rang de l'espèce, dont le diprotodontidae Hulitherium tomasettii, le kangourou Protemnodon tumbuna, et le thylacine Thylacinus cynocephalus. Les restes de Protemnodon tumbuna et d'un grand macropode non identifié ont été directement datés à 27‐22000 ans, une fourchette chronologique cohérente avec les datations radiocarbone. Il s'agit d'âges minimums en raison de la possible assimilation post‐dépositionnelle de 238U et de reprise stratigraphique. Les analyses palynologiques indiquent que des forêts de montagnes perhumides dominées par Nothofagus ont persisté, sans grande perturbation anthropique, depuis au moins 26‐20000 ans jusqu'au Pléistocène final. Les analyses de collagène (ZooMS) témoignent aussi du potentiel d'identification des restes mégafauniques de Nombe dans le futur. Cette étude laisse ouverte la possibilité d'une coexistence étendue entre des espéces de mégafaune dans les forêts tropicales de Nouvelle Guinée et les visites intermittentes de groupes humains, et souligne l'importance de poursuivre l'étude de ce site. Bien que préliminaires, ces résultats montrent qu'une meilleure connaissance des temporalités propres aux espèces et de l'impact anthropique sur les habitats sont indispensables aux débats sur les extinctions de mégafaune à travers le continent.